Prospective comparison of clinical and computed tomography assessment in detecting uterine perforation with intracavitary brachytherapy for carcinoma of the cervix. Issue 4 (1st July 2007) - Barnes, E. A.; Thomas, G.; Ackerman, I.; Barbera, L.; Letourneau, D.; Lam, K.; Makhani, N.; Sankreacha, R.
Abstract : Brachytherapy (BT) is an essential component of radical treatment for cervix cancer. Uterine perforation is a potential complication of intrauterine applicator (tandem) insertion. Postprocedure pelvic computed tomography (CT) scans are routinely performed at this center. The objective of this study was to prospectively compare radiation oncologists' (RO) clinical impression of satisfactory tandem placement with actual tandem placement as determined from pelvic CT. Patients with cervix cancer undergoing low–dose rate BT from April 2003 to December 2005 were prospectively identified. After tandem placement, patients were brought to the radiotherapy department for pelvic imaging (plain films and CT). Prior to viewing imaging, the RO specified whether they were concerned vs not concerned about uterine perforation. The CT was then reviewed to determine actual tandem placement (perforation vs no perforation). One hundred twenty-four sequential tandem insertions were performed in 114 patients and eligible for analysis. The incidence of CT detected uterine perforation was 13.7% (17/124). Physician concern, age greater than or equal to 60, and tumor size were significant predictors of uterine perforation ( P < 0.0001, P = 0.0019, and P = 0.0016, respectively). The overall sensitivity and specificity for physician concern was 52.9% and 84.1%, respectively. CT detected perforation in 8.2% (8/98) of insertions where the RO was clinically confident of correct tandem placement. Pelvic CT was a useful modality to accompany clinical assessment in identifying uterine perforation in cervix BT. As a low but potentially clinical significant number of perforations identified on CT were not suspected clinically, we recommend acquiring pelvic imaging in all patients following tandem insertion to ensure intrauterine tandem positioning.